Windows 8.1 inside out - Northrup, Tony, 1974- (Inside out (Redmond, Wash.), 2013)
A reference for experienced Windows 8.1 users provides hundreds of time-saving solutions, troubleshooting tips, and workarounds for topics ranging from personalization and input features to file managing and digital media syncing.